2021
DOI: 10.1002/jca.21929
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide practices in the use of central venous catheters for therapeutic plasma exchange in the inpatient setting

Abstract: Introduction: Therapeutic plasma exchange (TPE) is often impacted by difficulties in obtaining an adequate and safe vascular access. This study evaluated the rates, predictive factors, and clinical outcomes associated with central venous catheter (CVC) use during the inpatient TPE procedures. Methods:The Nationwide Readmissions Database, 2016 to 2017 was used to identify hospitalizations with TPE with and without CVC insertion. Results: During the study period, there were 35 429 hospitalizations with TPE (pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Our finding of a high prevalence of CVC use is consistent with data showing that CVCs are the most commonly used venous access type for TPE in the US 1,3,40 . A Nationwide Readmissions Database study of CVC use in TPE showed higher rates of CVC use among adults (73%) and children (74%) 3 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding of a high prevalence of CVC use is consistent with data showing that CVCs are the most commonly used venous access type for TPE in the US 1,3,40 . A Nationwide Readmissions Database study of CVC use in TPE showed higher rates of CVC use among adults (73%) and children (74%) 3 .…”
Section: Discussionsupporting
confidence: 90%
“…A national survey of apheresis providers in the American Society for Apheresis (ASFA) showed that CVCs are the preferred method for vascular access for therapeutic apheresis procedures 40 . In a nationwide study of TPE, predictors of CVC use were obesity (18% vs. 16%, P = 0.017), concurrent hemodialysis (14% vs. 10%, P < 0.001), female sex (54% vs. 50%, and illness severity ( P < 0.001) 3 . CVC has been preferred over peripheral venous access due to access difficulties, longer procedural times, suboptimal blood flow, inadequate process volume, and decreased efficiency 2,7,40‐42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 However, depending on the region studied, there is a wide range in the prevalence of CVC use (25%-73%). 38,39 Bleeding complications associated with CVC use are noted in a number of studies. In a study of 381 TPE procedures in 63 patients, severe complications occurred in four patients with CVC (6%).…”
Section: Timing Relative To Central Venous Catheter Placementmentioning
confidence: 99%
“…In an International Apheresis Registry report, central venous catheter (CVC) was the primary access method for TPE procedures in North and Central/South America (90% and 87%, respectively) 38 . However, depending on the region studied, there is a wide range in the prevalence of CVC use (25%‐73%) 38,39 …”
Section: Effects Of the Tpe Proceduresmentioning
confidence: 99%